Answer:
2x^2+4x-30=0
Step-by-step explanation:
2x^2+10x-6x-30=0
2x(x+5)-6(x+5)=0
(2x-6)(x+5)=0
2x-6=0 x+5=0
x=6/2 x=-5
x=3
Answer:
b) ? = 0
c) ? = 10
Step-by-step explanation:
By observing the equations, we notice a pattern. The resulting number is always equal to one number doubled added to the other number. Therefore, set up two equations as follows:
2(7)+y=14
2x+3=23
Assume that the provided number is the doubled number if it is a perfect factor, with 2, and assume the provided number is not the provided number if the difference between the answer and it is an even number.
Solve:
14+y=14
y=0
2x+3=23
2x=20
x=10
Answer:
2,2,3,4,5
Step-by-step explanation:
Just show how to get the mean, median, mode, and range to justify the answer
Also hey Brailen